Waste, recycling and reuse - "Morgan, Sally" (Sterling Publishers New Delhi, 2006)
"Waste, Recycling and Reuse," published by Sterling Publishers Pvt. Ltd. This English-language book is available in both hardcover and paperback editions. It explores topics related to waste management, recycling, and reuse.